Software development for water pricing model - Wee, Aida Sze Chia (2006)
Water scarcity in terms of quantity and quality leads to increase cost of supplying water to users. The major concerns faced by the water industry are low tariffs that result in insufficient revenue to cover the costs of supplying water and cheap water that discourage water conservation. Underpricing has seriously affected the finances of service providers, and resulted in poor and unreliable water services. Water pricing is an essential component which is instrumental in achieving two important goals: to generate revenue for capital recovery, operation and maintenance, extension and upgrading of the system; and to promote efficiency in use. Hence water pricing model is developed in this study to generate appropriate water tariff that enables water utilities and regulatory bodies to balance the benefits and costs of water usage, and to ensure sufficient revenue for the long term financial sustainability of the water supply business. Visual Basic 6.0 was selected as a tool to develop the water pricing model due to its object-oriented programming. The water pricing model developed provides a user-friendly approach to access to essential knowledge on the water sector in Malaysia, emphasising the economic aspect, and the procedures to calculate the price of water. In the model developed, the price of water was calculated based on capital expenditures (CAPEX) and operating expenditures (OPEX), applying the principle of full cost recovery and partly subsidising the consumers. The water pricing model is limited to calculate water tariffs for domestic residential homes, and industrial and commercial supplies. The model also provides justifications for any adjustment to the current levels of water tariffs. This was obvious that the water pricing model developed in this study acts as an important tool in revising the current water tariffs to ensure the sustainability of water service provision.